2014
DOI: 10.5334/tohm.189
|View full text |Cite
|
Sign up to set email alerts
|

Change in Non-motor Symptoms in Parkinson’s Disease and Essential Tremor Patients: A One-year Follow-up Study

Abstract: Background: Non-motor symptoms (NMS) in Parkinson's disease (PD) differ from those in essential tremor (ET), even before a definitive diagnosis is made. It is not clear whether patient's knowledge of the diagnosis and treatment influence their subsequent reporting of NMS.Methods: 1 year after a clinical and instrumental diagnosis, we compared the motor impairment (Movement Disorders Society (MDS)-Unified Parkinson's Disease Rating Scale-III) and non-motor symptoms (NMSQuest) in PD (n531) and ET (n521) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
1
Order By: Relevance
“…Few previous studies have explored the clinical features of this combination. These studies have indicated the possible presence of several differences in MFs 2 4 , 8 , 11 and NMFs 12 , 13 between patients with isolated ET and their ET→PD counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…Few previous studies have explored the clinical features of this combination. These studies have indicated the possible presence of several differences in MFs 2 4 , 8 , 11 and NMFs 12 , 13 between patients with isolated ET and their ET→PD counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…Research focused on NMS among individuals with ET is just emerging, but recent studies suggest some important differences between those with PD and those with ET in the frequency and type of NMS reported. 10,11 Despite the prevalence of these disorders and growing awareness of the impact of NMS on QOL, little is known about patient-reported needs and barriers to care of individuals with MDs. While patient needs related to the motor and non-motor symptoms of MDs are…”
Section: Introductionmentioning
confidence: 99%
“…Research focused on NMS among individuals with ET is just emerging, but recent studies suggest some important differences between those with PD and those with ET in the frequency and type of NMS reported. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%